Persons Authorized for Court Desicion Appeal - Rokva, Irine (European Scientific Journal, ESJ, 2023)
The study aims to give equal time to the issue provided by the Civil Procedure Code - the person’s access to one of the legal mechanism - one of the prerequisites- not to review party’s claim without any complaint (appeal, cassation, the private complaints). This, therefore, is linked to the subjects of the determination of the appeal court’s decision. The Civil Procedure Code (Code of Civil Procedure, Article 364, Article 391 of the first part, the second part of Article 414) refers to the circle of persons having the right to appeal the court decision. Such persons include the parties and third parties with an independent request. In the court practice, this problem arose concerning such persons who do not belong to the above mentioned list and are: a) persons who may not participate at any capacity in a particular dispute (the contested decision in particular, not this or that dispute in general), however, the decision directly affected their legal rights; b) third parties who claim to be submitted to the Independent, which also are undoubtedly interested in the outcome. This issue resulted to dissension among scientists, as well as the different legal practice. However, in recent years, the legal judicial tried in solving the problem. From the Supreme Court’s practice, which is the instance that states the court practice, it turns out that the right of claim in the Court of Appeal and Cassation has persons who are substantially affected by the challenged decision. Nevertheless, the Court of Cassation in its judgments directly and clearly did not reply to the question of whether third parties without any independent request have the private right of appeal. The analysis provides the basis for admission to the practice of reasonable doubt. It states that the above-mentioned persons have the right to appeal against the decisions, whether and to what extent is the contested decision and, in particular, the operative part of these legal interests. Thus, the present study confirmed the relevance of these issues as a scientific and practical arena arising divergence. The task, however, posed the problem of the rate of the first civil procedural law and, on the other hand, the practice originated based on the legal basis of needs that require specific ways. This is aimed at preventing the right of access to undue restrictions and specific legal persons concerned in court to appeal the decision unlawful rejection course.